an Analysis of Warning Icons Used on Food and Beverages Carton (Semiotics Approach) - Wijayanti, Kharisma Sri (2007)
Our daily life aspects are full of signs including icon, index, and symbol. The aims of this research are to describe the meanings and the reasons of the warning icons used on foods and beverages cartons. The theories used are the Saussure's theories and The Barthes' theories. Saussure emphasized his theory in analyzing the sign using the signifier and signified criteria. Then, Barthes emphasized his theory on the myth that derived from the denotative and connotative levels. The type of this research is qualitative interpretative type. In collecting the data, the writer applied the documentation and observation methods. The several steps are done to analyze the data. In analyzing the meaning, the steps are: analyzing the signifier, analyzing the signified, and analyzing the text. In analyzing the reasons, the steps are: analyzing the denotation level, analyzing the connotation level, and analyzing the myth. This research shows the variety of the meanings and the reasons of the warning icons used on the foods and beverages icons. The meanings are: 1) referring to the cartons, such as: the warning to avoid the cartons from the wet or moisture and the heat, the warning to avoid the cartons from the strong smell, the warning that the cartons should be bought carefully, the warning that the carton are not allowed to tread and give the load amount, the warning not to put the carton facing backwards, the warning of the maximum amount piles, the warning to avoid the cartons from the direct contact to the floor, and the warning that the cartons should be put in the right order; 2) referring to the users: the warning of the maximum amount piles; 3) referring to both cartons and users: the warning of the maximum amount piles. The reasons are: the popularity reasons, the acceptability reasons, the characteristic similarity reasons, and the clarity reasons.